Feminist Pedagogy in the Neoliberal University: The Limits of Precarious Labour - Potvin, Jacqueline; Dority, Kimberly (Atlantis)

(untitled) (Mount Saint Vincent University, 2022)
In recent years, feminist pedagogy has been advanced as a strategy for disrupting the neoliberal corporatization of the university classroom. In this paper, we both recognize and trouble this disruptive potential, examining how the working conditions faced by adjunct instructors affect our ability to put our commitments to feminist pedagogy into practice. Based on our own experiences as sessional instructors, we argue that conditions such as heavy workloads, alongside limited access to institutional resources and community, contribute to faculty burn-out and hinder our ability to build and maintain feminist student-instructor relationships. Drawing on existing scholarship on feminist pedagogy, and emerging work exploring the challenges of teaching within the neoliberal university, we argue for the need to extend and complicate dominant understandings of feminist pedagogy as a series of values and practices that individual instructors can implement, and to recognize how its enactment is limited by the adjunctification of higher education. This paper pertains to instructors, particularly those in feminist departments, seeking to apply feminist pedagogy across the university.